Early Empirical Tuberculosis Treatment in HIV-Positive Patients Admitted to Hospital in South Africa: An Observational Cohort Study. (31st March 2021) - Bresges, Carolin; Wilson, Douglas; Fielding, Katherine; Corbett, Elizabeth L; Del-Greco, Fabrizia; Grint, Daniel; Peters, Jurgens; Gupta-Wright, Ankur
Abstract: Background: Empirical tuberculosis (TB) treatment in human immunodeficiency virus (HIV)–positive inpatients is common and may undermine the impact of new diagnostics. We sought to describe empirical TB treatment and compare characteristics and outcomes with patients treated for TB after screening. Methods: This was a retrospective observational cohort study of HIV-positive inpatients treated empirically for TB prior to TB screening. Data on clinical characteristics, investigations, and outcomes were collected from medical records. Comparison cohorts with microbiologically confirmed or empirical TB treatment after TB screening with Xpert MTB/RIF and urine lipoarabinomannan assays were taken from South African Screening for Tuberculosis to Reduce AIDS-Related Mortality in Hospitalized Patients in Africa (STAMP) trial site. In-hospital mortality was compared using a competing-risks analysis adjusted for age, sex, and CD4 cell count. Results: Between January 2016 and September 2017, 100 patients excluded from STAMP were treated for TB empirically prior to TB screening. After enrollment in STAMP and TB screening, 240 of 1177 (20.4%) patients received TB treatment, of whom 123 had positive TB tests and 117 were treated empirically. Characteristics were similar among early empirically treated patients and those treated after TB screening. 50% of early empirical TB treatment was based on radiological investigations, 22% on cerebrospinal or pleural fluid testing, and 28% on clinical features alone. Only 11 of 100 empirically treated patients had subsequent microbiological confirmation. In-hospital mortality was lower in patients with microbiologically confirmed TB compared to those treated empirically (adjusted subdistribution hazard ratio, 0.5 [95% confidence interval, .3–.9). Conclusions: Empirical TB treatment remains common in severely ill HIV-positive inpatients. These patients may benefit from TB screening using existing rapid diagnostics, both to improve confirmation of TB disease and reduce overtreatment for TB. Abstract : Early empirical tuberculosis (TB) treatment in HIV-positive inpatients is common, with patients having similar characteristics but higher mortality than those with microbiological confirmation of TB. This group may benefit from rapid TB diagnostics improve confirmation of TB disease and reduce over-treatment.